Merajut Masa Depan Pesantren: Reformasi Kebijakan untuk Integrasi dan Satu Data Pendidikan - Agustina Purnairawati (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes that integration of traditional Islamic boarding schools (pesantren khalafiyah) with formal education (madrasah) in Indonesia faces significant structural and administrative challenges. The urgency of this issue stems from the ambiguity of legal status, an excessive administrative burden, and fragmented educational data. These problems impede operational effectiveness, threaten the quality of education, and undermine public trust in these hybrid institutions. This situation also complicates access to government funding and legal recognition for graduates. This policy paper utilizes a problem analysis approach supported by USG (Urgency, Seriousness, Growth) analysis and a fishbone diagram to identify the root causes of the issues. The analysis confirms that the lack of clear legal status is the most critical issue, which in turn gives rise to other problems such as threats to educational quality and data fragmentation. The research findings indicate that a key problem is the existence of dual regulations and a lack of policy harmonization between different directorates within the Ministry of Religious Affairs. This regulatory duality results in separate reporting systems and redundant administrative procedures for integrated institutions. The results of this analysis highlight four main issues: unclear institutional status, a direct threat to education quality, fragmented educational data, and cumbersome administration. Resolving these issues is crucial for empowering pesantren khalafiyah and strengthening the foundation of national education, in line with the government's vision to develop competitive human resources.